Inverse design of reconfigurable piezoelectric topological phononic plates - Xiaoying Zhuang; Chuong Nguyen; S.S. Nanthakumar; Ludovic Chamoin; Yabin Jin; Timon Rabczuk (Materials & Design, 2022)
We present a methodology to perform inverse design of reconfigurable topological insulators for flexural waves in plate-like structures. A genetic algorithm based topology optimization method is developed and a C6v plate unit cell topology that offers twofold degeneracy in the band structure is designed. Piezoelectric patches, that are connected to an external circuit, are bonded to the substrate plate and are altered appropriately to break space inversion symmetry. The space inversion symmetry breaking opens a topological band gap mimicking quantum valley Hall effect. Numerical simulations demonstrate that the topologically protected edge state exhibits wave propagation without backscattering and is immune to disorders. The present work achieves real-time reconfigurability of the topological interfaces for waveguide applications.